Measurement, reporting and verification of greenhouse gas emissions from livestock: current practices and opportunities for improvement - Wilkes, Andreas (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Greenhouse gas (GHG) emissions from agriculture now exceed emissions from land use, land use change and forestry, including deforestation, and are growing at a rate of about 1% per year (Tubiellio et al. 2015). The main livestock emission sources – enteric fermentation, manure management and manure deposited on pasture – account for 62% of all agriculture emissions (FAOSTAT).